2009
DOI: 10.1073/pnas.0906861106
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal analytical approaches to detect potential contaminants in heparin

Abstract: Heparin is a widely used anticoagulant and antithrombotic agent. Recently, a contaminant, oversulfated chondroitin sulfate (OSCS), was discovered within heparin preparations. The presence of OSCS within heparin likely led to clinical manifestations, most prevalently, hypotension and abdominal pain leading to the deaths of several dozens of patients. Given the biological effects of OSCS, one continuing item of concern is the ability for existing methods to identify other persulfonated polysaccharide compounds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 37 publications
2
77
1
Order By: Relevance
“…S2B). Consistent with our published observations that the heparins are not contaminated with OSCS alone (7,8); the published CE data (6,34) also showed that an OSHS co-migrated with heparin (see Ref. 6, supplemental Fig.…”
Section: Chemically Oversulfated Gags Were More Sulfated Thansupporting
confidence: 79%
See 2 more Smart Citations
“…S2B). Consistent with our published observations that the heparins are not contaminated with OSCS alone (7,8); the published CE data (6,34) also showed that an OSHS co-migrated with heparin (see Ref. 6, supplemental Fig.…”
Section: Chemically Oversulfated Gags Were More Sulfated Thansupporting
confidence: 79%
“…One peak was named fully sulfated CS and the other was named partially sulfated OSCS in the published report (34). In addition, we found that less sulfated DS and HS (OSDS-M, OSDS-L and OSHS-M, OSHS-L) had several proton signal peaks such as 2.04, 2.07, 2.10, and 2.12 ppm for OSHS-M and OSHS-L and/or OSDS-M and OSDS-L, which made the 2.07 Ϯ 0.02 and 2.12 Ϯ 0.02 ppm proton chemical shifts not specific for DS and OSDS, respectively, in contrast to the published reports (6,34). Because the heparin contaminant that migrated before heparin, based on CE analysis, was defined as OSCS or heparin contaminant during the past 2 years, we decided to choose all the OSGAGs that migrated like OSCS (Fig.…”
Section: Chemically Oversulfated Gags Were More Sulfated Thancontrasting
confidence: 51%
See 1 more Smart Citation
“…3). Structural integrity of gel-eluted oligosaccharides was assessed by two-dimensional correlation spectroscopy (2D COSY) and 2D heteronuclear multiple quantum coherence (2D HMQC) spectroscopy [20]. Comparison of the 2D COSY and 2D HMQC spectra of the BLH oligosaccharide mixture and gel-eluted oligosaccharides confirmed that the saccharide backbone structure remains unchanged after the CE-PAGE (Fig.…”
Section: Nmr Analysismentioning
confidence: 95%
“…5 The less sulfated GAGs are removed from crude heparin during pharmaceutical grade heparin production into two heparin byproducts named GAG waste and tank bottom. 6 GAG waste has a NMR profile highly resembles heparin 6 but it consists of less sulfated heparin/heparan sulfate and dermatan sulfate. The tank bottom consists of even less sulfated heparan sulfate, chondroitin sulfate, and dermatan sulfate.…”
Section: Introductionmentioning
confidence: 99%